Regularizaç\~ao fundiária no Brasil: Avanços e desafios - Raúl V. Gómez; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– A vast economic literature argues that well-defined property rights over land use can be associated with increases in efficiency in the use of scarce resources. In December 2020, the Brazilian government launched the Titula Brasil program, which aims to support and facilitate the land regularization process in the country. The process of regularization of settlers has become a debate of interest regarding the national agrarian policy, since the agrarian sector is responsible for a considerable portion of the national economy. Given the above, this work sought to investigate the relationship between property rights over land use, measured as the number of titles issued and various economic results in the agricultural sector. The results show a positive relationship between the number of domain titles and the value of production and the area planted in Brazilian states during the period from 2019 to 2021. The general perception is that policies that seek to strengthen property rights can contribute to the economic development of the agricultural sector. However, causality analysis is necessary to estimate the effects of this type of policy.
10419/284907
Keywords: Q10; Q15; Q18; 330; property rights; production value; agricultural production